Romania : Staff Report for 2004 Article IV Consultation and Request for Stand-By Arrangement. (IMF Staff Country Reports; Country Report, 2004)
Romania's 2004 Article IV Consultation and Request for Stand-By Arrangement (SBA) are discussed. The authorities have requested a new precautionary 24-month SBA to secure macroeconomic stabilization and keep European Union accession on track. Romania has preserved competitiveness, despite the slowdown in depreciation and recently strong domestic demand. Exports remained the strongest component of aggregate demand and Romania continued to increase market share in its main trading partners. An exchange-rate-based monetary policy has been successful in accomplishing disinflation but has faced challenges in containing credit growth.